Late postoperative stenosis of the intermediate bile duct - Bergalli, Luis E.; Piacenza, Guillermo; Chifflet, Juan; Gateño, Nisso; Estefan, Alberto; Priario, Julio; Praderi, Raúl C. (Cirugía del Uruguay, 1975)
The authors report 3 observations of late stenosis of the intermediate extrahepatic hile duct, following operations in which the continuity of the bile duct was not interrupted. The clínica] signs occurred late and they suggested completely different pictures to trose found in the surgical act. All of them were fibro-sclerotic strictures of the hepato-cystic-choledochus confluence, non-neoplasic, and without any apparent etiological cause. They were solved by biliary-digestive derivation or end-to-end reconstruction of the bile duct when both ductal ends were of a similar caliber. A tube was always placed through the anastomosis, to act as a stent of it